Analisis Trafo Scott Mengatasi Penurunan Kapasitas Daya Akibat Distorsi Harmonik - Jaka Suprapto; Chairul G Irianto; Riki Ruli A. Siregar (Energi & Kelistrikan, 2020)
This study aims to determine Scott's transformer size which is suitable for use in the electrical system of the 4th Floor, F&G Building, Herry Hartanto Building, Faculty of Industrial Technology, Trisakti University. found in the electrical system. The research used is a quantitative and qualitative approach. This quantitative study was used because the researchers wanted to know and calculate the magnitude of the harmonics that occurred on the 4th Floor, F&G Building, Herry Hartanto, Faculty of Industrial Technology, Trisakti University and designed a single passive tuned filter parameter. Whereas qualitative research was used to analyze the comparison between before and after the installation of Scott transformers and their effect on the harmonic value of the 4th Floor, F&G Building, Herry Hartanto, Faculty of Industrial Technology, Trisakti University. The results of this study are the simulation results of the Scott relationship transformer installation can eliminate voltage harmonics so that the electric waves formed into pure sine and Scott transformer connection installation can reduce the highest THD value in panel A, Floor 4, Building F&G, Herry Hartanto Building, Faculty of Technology Industry, Trisakti University from 11.45% to 1.28x10-5%